(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article explores the theoretical foundations and practical applications of modern testing and evaluation systems used to assess the physical fitness of athletes and students. Physical fitness is directly related to an individual’s overall health, performance efficiency in sports, and social engagement. Objective and reliable assessment of physical readiness plays a critical role in promoting a healthy lifestyle and guiding personalized training approaches. The article reviews internationally recognized testing protocols, such as walking/running tests, upper body strength assessments, and maximal oxygen uptake (VO₂ max) analysis, as well as technologically advanced tools including motion sensors, heart rate monitors, and GPS-based tracking systems. Special attention is given to the use of normative standards, individualized evaluation criteria, and the integration of automated systems for data collection and analysis. The implementation of modern fitness assessment systems contributes significantly to designing customized training programs, controlling rehabilitation processes, and forecasting athletic potential in educational and competitive environments.